2021
DOI: 10.3389/fnut.2021.646694
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Single-Item Self-Rated Diet Construct With Diet Quality Measured With the Alternate Healthy Eating Index

Abstract: Background: A single-item self-rated diet measure (SRD) may provide a quick, low-burden screener. However, assessment of its validity is limited. This study aimed to evaluate the association of an SRD construct with measured diet quality among adults in Puerto Rico (PR).Methodology: Participants (30–75 years old; n = 247) of the PR Assessment of Diet, Lifestyle, and Diseases (PRADLAD) cross-sectional study reported SRD with a single question (“How would you describe your current dietary habits and diet quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Previous studies have shown that self-rated fat intake is a valid measure for evaluating diet quality at the population and it also provides a simple method for identifying people with worst diet quality. 27 28 …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that self-rated fat intake is a valid measure for evaluating diet quality at the population and it also provides a simple method for identifying people with worst diet quality. 27 28 …”
Section: Methodsmentioning
confidence: 99%
“…39 The association between older age and a reduced likelihood of perceiving a need to improve diet aligns with previous reports of higher self-ratings of dietary quality in older age groups, 38,39 while the greater likelihood of females perceiving a need to improve diet in the dietary components model diverges from reported similarities across men and women in perceptions of dietary healthfulness. 40,41 This discrepancy may be attributed to the difference in asking participants to consider whether they need to improve their diet, which is distinct from rating the healthfulness of their diet. 38,40 In their study of people LWBC, Xue et al asked participants to rate how healthy their diet was on a scale of one to five, while Batis et al asked participants a closed binary question of whether they considered their diet to be healthy.…”
Section: Discussionmentioning
confidence: 99%
“…35 In Xue et al's study, each 10-year increase in age was associated with greater odds of being incorrectly optimistic about dietary quality, 38 while different age groups had a differential effect on being incorrectly optimistic in Variyam et al's study of the general population. 36 While there are only few studies examining predictors of misperceptions of dietary quality, 36,38 previous research is inconclusive regarding associations between dietary quality perception (whether correct or not) and demographic factors such as age [38][39][40][41] and sex. 37,38,40 While, Batis et al and Gago et al observed similarities in the mean ages of participants across differing perceptions of dietary quality, 40,41 Sullivan et al reported that adults, who perceive their diet to be of higher quality tend to be older than those who report lower self-ratings of dietary quality.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations